2011
DOI: 10.1103/physrevb.84.174502
|View full text |Cite
|
Sign up to set email alerts
|

Precision global measurements of London penetration depth in FeTe0.58Se0.42

Abstract: We report tunnel diode resonator measurements of in-plane London penetration depth, λ(T ), in optimally-doped single crystals of Fe(Te0.58Se0.42) with Tc ∼ 14.8 K. To avoid any size-dependent calibration effect, six samples of different sizes and deliberately introduced surface roughness were measured and compared. The power-law behavior, ∆λ(T ) = AT n , was found for all samples with the average exponent navg = 2.3 ± 0.1 and the pre-factor Aavg = 1.0 ± 0.2 nm/K 2.3 . The average superfluid density is well des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
35
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 36 publications
9
35
1
Order By: Relevance
“…[50] by the average and standard deviation of measurements on 12 crystals) for pure samples. The values at the lower boundary of the error bars provided the best agreement with TDR skin depth measurements, due to being less prone to cracks [51]. Within rather big error bars of the resistivity measurements, the resistivity value for Na-doped samples is indistinguishable from that of the pure material at high temperatures, so we adopted the same ρ(300 K).…”
Section: Resultsmentioning
confidence: 97%
“…[50] by the average and standard deviation of measurements on 12 crystals) for pure samples. The values at the lower boundary of the error bars provided the best agreement with TDR skin depth measurements, due to being less prone to cracks [51]. Within rather big error bars of the resistivity measurements, the resistivity value for Na-doped samples is indistinguishable from that of the pure material at high temperatures, so we adopted the same ρ(300 K).…”
Section: Resultsmentioning
confidence: 97%
“…Our answer is the following. We believe that the earlier data on Fe(Te,Se) crystals (including those of Klein et al) [2,12,21] represent the dirtier cases, whereas the sample in our more recent study [11] is closer to the clean behavior. Therefore, fitting the superfluid density with a clean -limit self -consistent two -gap model in the full temperature range is still justified at least in Ref.…”
mentioning
confidence: 45%
“…London penetration depth was measured after each step. It was found that the penetration depths measured before and after razor-blade damaging didn't show any significant change and we concluded that roughness plays only a minor role, even for a very strong damage [11] …”
mentioning
confidence: 96%
See 2 more Smart Citations